The Association of Body Image Self-Discrepancy With Female Gender, Calorie-Restricted Diet, and Psychological Symptoms Among Healthy Junior High School Students in Japan - Nomura, Kyoko; Itakura, Yuki; Minamizono, Sachiko; Okayama, Kazuyo; Suzuki, Yumiko; Takemi, Yukari; Nakanishi, Akemi; Eto, Kumi; Takahashi, Hitoshi; Kawata, Yuki; Asakura, Hitomi; Matsuda, Yorika; et al. (Frontiers in Psychology, 2021)
Background: Body image self-discrepancy reflects a preference for weight loss regardless of normal body size and is a distorted cognition that may be a precursor to eating disorders. The aim of this study was to investigate factors associated with body image self-discrepancy among healthy junior high school students in Japan. Method: This cross-sectional study was conducted at one junior high school in Saitama, Japan, in December 2016. After excluding obese participants (defined as 20% above their ideal weight), 304 students (mean age, 13.9 years; n = 181 girls, 59.5%) who fell into underweight (n = 22, 7.2%) and normal weight categories were selected. Body image self-discrepancy was measured using the Contour Drawing Rating Scale which include eight separate figures representing body sizes. We then calculated the difference by subtracting ideal from current body sizes and defined body image self-discrepancy if the difference >1. Results: Girls constituted 92% (n = 49) of the 53 students with body image self-discrepancy. In all students, multivariable stepwise models demonstrated that female gender (OR, 6.92, 95% CI: 2.33–20.51), a calorie-restricted diet (OR, 5.18, 95% CI: 2.22–12.05), and psychological symptoms (OR, 1.47, 95% CI: 1.15–1.87) were significantly associated with an increased risk of body image self-discrepancy. Specifically for girls, an increased risk of body image self-discrepancy was associated with calorie-restricted suppers and psychological symptoms. Conclusion: Body image self-discrepancy among healthy adolescents in Japan was found to be closely linked to being a girl, having a calorie-restricted diet, and having psychological symptoms.